Mempelajari Pengeringan Lapis Tipis Pisang Ambon - Linasari, Linasari; Tamrin, Tamrin; Rahmawati, Winda; Kuncoro, Sapto (Jurnal Agricultural Biosystem Engineering, 2023)
This research aims to study the effect of temperature and banana varieties on changes in physical and chemical properties of banana’s sale after drying.  The study was conducted by an experimental method with two treatments namely drying temperature and banana varieties.  The parameters observed were initial water content, equilibrium water content (Me), drying constants (k), vitamin C, and color.  The results showed that the banana varieties (Green Ambon and White Ambon) did not affect the drying time, equilibrium water content (Me), and drying constants but did affect the final water content, vitamin C, and the panelists' preference level towards the sale colors of bananas produced.  While the drying temperature used affects all observed parameters.  Low temperature (± 50 ℃) is the optimal temperature because the temperature produces yellowish-brown banana color (Cinnamon) on both banana varieties with a preference level of 44.45% very like, the final water content of 15.28% bb with a long drying time of 38.67 hours on Green Ambon bananas, while on White Ambon bananas are 55.56% like, the final water content of 16.55% bb and drying time of 38.50 hours. Keywords: Banana Sale, Chemical Properties, Drying, Physical, Thin Layer.